The Role of Gender in Ophthalmology Resident Evaluations - Birnbaum, Faith A.; Chandramouli, Shivram; Thomas, Mridul K.; Rosdahl, Jullia A. (Journal of Academic Ophthalmology, 2020)
Background Gender affects various aspects of medical training. Prior research in surgical specialties has shown that female residents are given less positive feedback, granted less autonomy in the operating room, perform fewer procedures, and achieve competency milestones at a slower rate as compared with their male counterparts.Purpose The purpose of this research is to evaluate whether gender affects ophthalmology resident evaluations at a single institution.Methods Ophthalmology resident evaluations at a single residency program from 2010 to 2018 were reviewed. Data were collected on faculty gender, resident gender, and year of resident training. A linear mixed-effects model was utilized to analyze the degree to which differences in evaluation scores could be predicted from demographic data, while accounting for multiple sources of nonindependence of data.Results A total of 490 evaluations for 43 residents by 34 faculty were analyzed. Evaluations consisted of up to 23 questions graded on a scale from 0 (poor) to 9 (excellent). Female residents received marginally higher scores than male residents on average (coefficient of male residents = −0.2). Both male and female residents received marginally lower scores from male faculty than from female faculty on average (coefficient of male faculty = −0.21). Male faculty also appeared to have scored male residents lower to a greater degree than did female faculty (coefficient of male faculty by male resident interaction = −0.14), though this result was sensitive to model specifications. There was no significant interaction between year of resident training and gender.Conclusion In contrast to other procedural specialties, female residents appear to have been graded at a similar level or higher than male residents on average. Male faculty gave slightly lower scores to both male and female residents than female faculty did. Male faculty also may have graded male residents marginally lower than female residents to a greater degree than female faculty did.
Keywords: ophthalmology; resident education; medical education; disparity; gender